Expanding the Carbene CH Insertion Toolbox. Issue 4 (22nd January 2015) - Morton, Daniel; Blakey, Simon B.
<x xml:space="preserve">Abstract</x> A Bigger toolbox: Two recent discoveries demonstrate significant advances in the controlled generation and CH insertion chemistry of the previously inaccessible donor–donor and alkyl–alkyl classes of metallocarbenes. These discoveries lay the groundwork for broad reaction development with these versatile reactive species. EDG=Electron‐donating group; EWG=Electron‐withdrawing group; M=Transition metal.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>